Frame Work Of Sensor In Smart House Using Orange Technology. - Melyani Melyani (University of Science and Computer Technology, 2023)
Now days, the home environment is still much less supportive of life for the elderly, most elderly living at home need a companion to help them. Safety, health, happiness and independence will be difficult for them to get even the elderly will be further away from the surrounding environment. Based on population projection 2017 data there are 23.66 million elderly people in Indonesia and predicted in 2020 there are 27.08 million people elderly. Smart homes that are currently widely studied have not focused on elderly; most smart homes only provide a sense of security and convenience for adult residents. And this will be a problem that until now has not solved the improvement of human life through technology to get happiness, care and health especially for the elderly. In many cases of the elderly, it is easier to send them to live in a nursing home and that keeps them separated from their families for the rest of their lives. That's what makes them less happiness. Orange Technology is a collection of technological elements to improve human life by getting happiness, Care and health. This study reviewed the journals of scientific databases such as IEEE explore, ACM digital library and Proquest published from 2002 to 2017. From the search results obtained 54 papers that will answer the scientific questions of this research. The result of this research is a framework of smart house that has Sensor, Monitoring, Wireless, Scalability, Low cost, GPS and ease of installation and maintenance as components of smart house of orange technology for elderly.